In Vivo and In Vitro Toxicodynamic Analyses of New Quinolone-and Nonsteroidal Anti-Inflammatory Drug-Induced Effects on the Central Nervous System - Kita, Hideki (American Society for Microbiology, 1999)
We investigated the correlation between an in vivo isobologram based on the concentrations of new quinolones (NQs) in brain tissue and the administration of nonsteroidal anti-inflammatory drugs (NSAIDs) for the occurrence of convulsions in mice and an in vitro isobologram based on the concentrations of both drugs for changes in the γ-aminobutyric acid (GABA)-induced current response in Xenopus oocytes injected with mRNA from mouse brains in the presence of NQs and/or NSAIDs. After the administration of enoxacin (ENX) in the presence or absence of felbinac (FLB), ketoprofen (KTP), or flurbiprofen (FRP), a synergistic effect was observed in the isobologram based on the threshold concentration in brain tissue between mice with convulsions and those without convulsions. The three NSAIDs did not affect the pharmacokinetic behavior of ENX in the brain. However, the ENX-induced inhibition of the GABA response in the GABA(A) receptor expressed in Xenopus oocytes was enhanced in the presence of the three NSAIDs. The inhibition ratio profiles of the GABA responses for both drugs were analyzed with a newly developed toxicodynamic model. The inhibitory profiles for ENX in the presence of NSAIDs followed the order KTP (1.2 μM) > FRP (0.3 μM) > FLB (0.2 μM). These were 50- to 280-fold smaller than those observed in the absence of NSAIDs. The inhibition ratio (0.01 to 0.02) of the GABA(A) receptor in the presence of both drugs was well-fitted to the isobologram based on threshold concentrations of both drugs in brain tissue between mice with convulsions and those without convulsions, despite the presence of NSAIDs. In mice with convulsions, the inhibitory profiles of the threshold concentrations of both drugs in brain tissue of mice with convulsions and those without convulsions can be predicted quantitatively by using in vitro GABA response data and toxicodynamic model.